2016
DOI: 10.1002/iid3.136
|View full text |Cite
|
Sign up to set email alerts
|

Transient Treg depletion enhances therapeutic anti‐cancer vaccination

Abstract: IntroductionRegulatory T cells (Treg) play an important role in suppressing anti‐ immunity and their depletion has been linked to improved outcomes. To better understand the role of Treg in limiting the efficacy of anti‐cancer immunity, we used a Diphtheria toxin (DTX) transgenic mouse model to specifically target and deplete Treg.MethodsTumor bearing BALB/c FoxP3.dtr transgenic mice were subjected to different treatment protocols, with or without Treg depletion and tumor growth and survival monitored.ResultsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…The last phase of tumor progression is metastatic dissemination, a process well modelled by the 4T1 breast carcinoma derived from a BALB/c mouse. A moderate role for Treg in facilitating 4T1 primary tumor growth and precipitating death has been reported. Monitoring WT and Foxp3‐fGFP animals implanted subcutaneously with 4T1 cells revealed similar growth of the primary tumor while survival was significantly prolonged in the latter group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The last phase of tumor progression is metastatic dissemination, a process well modelled by the 4T1 breast carcinoma derived from a BALB/c mouse. A moderate role for Treg in facilitating 4T1 primary tumor growth and precipitating death has been reported. Monitoring WT and Foxp3‐fGFP animals implanted subcutaneously with 4T1 cells revealed similar growth of the primary tumor while survival was significantly prolonged in the latter group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FCM was used to detect the T‐cell subsets. As shown in Figures a – c , the proportions of different T‐cell subsets in the blood were measured by FCM. The proportions of CD4 + and CD8 + T‐cells in the combined group were the highest among the four groups ( p < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrence of solid tumors may be due to the inability of traditional chemotherapy and radiotherapy to eliminate CSCs . At present, therapeutic vaccines have been extensively used to induce endogenous tumor‐reactive T cells . We have developed a technology that immobilizes streptavidin (SA)‐tagged bioactive cytokines on the biotinylated tumor cell surface to prepare tumor cell vaccines.…”
mentioning
confidence: 99%
“…Studies in animals have demonstrated the ability Treg depletion to synergize with immunotherapy in a murine model of mesothelioma [84]. Importantly, studies investigating the utility of targeting Tregs in cancer patients identified a novel mechanism by which the administration of FDA-approved daclizumab, a monoclonal antibody which specifically targets CD25, selectively reprogrammed Tregs to produce IFN-gamma by driving the downregulation of FoxP3; this resulted in robust T cell responses against vaccine antigens without autoimmunity [85, 86].…”
Section: Strategies That Target Regulatory T Cells In Breast Cancermentioning
confidence: 99%